Toward a quantitative correlation between microstructure and DSSC efficiency: a case study of TiO2-xNx nanoparticles in a disordered mesoporous framework - Sivaranjani, Kumarsrinivasan; Agarkar, Shruti A.; Ogale, Satishchandra B.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
The efficiency (eta) of a dye-sensitized solar cell (DSSC) depends on various parameters, the critical factors being a fast charge carrier transport and a slow rate of electron-hole recombination. The present article describes a simple combustion synthesis method to prepare TiO2-xNx with following four important features that directly influences eta: (1) a disordered mesoporous structural framework with high surface area to give high dye-loading and a small diffusion length for charge carriers allowing rapid movement to the surface; (2) electrically interconnected nanocrystalline TiO2-xNx particles with good necking and predominant (101) anatase facets to minimize electron-hole recombination; (3) low charge storage capacity in the titania framework; and (4) surface unsaturation assisting all the above factors. The pseudo-three-dimensional nature of mesoporous TiO2-xNx with the above features demonstrates the importance of textural features, and porosity allows faster diffusion of charge carriers to surface and their utilization to generate power. A quantitative correlation between interconnected nanoparticles over larger distances in a mesoporous framework and eta is demonstrated. This study also demonstrates an inexpensive and rapid method of producing the photoanode material with high eta in about 10 min.